2023
DOI: 10.1002/eat.23989
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorder psychopathology, psychiatric impairment, and symptom frequency of atypical anorexia nervosa versus anorexia nervosa: A systematic review and meta‐analysis

Abstract: ObjectivesRestrictive eating disorders (EDs) occur across the weight spectrum, but historically more focus has been given to anorexia nervosa (AN) than atypical anorexia nervosa (atypAN). AtypAN's relegation to a diagnosis in the “other specified feeding and eating disorder” (OSFED) category and paucity of research surrounding atypAN invariably implies a less clinically severe ED. However, a growing body of research has begun to question the assumption that atypAN is less severe than AN. The current review and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
23
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 69 publications
7
23
1
Order By: Relevance
“…Endorsing these cognitive aspects of AN was also highly correlated with the severity of weight loss, but not the time frame of weight loss, highlighting the complexity and importance of further research to delineate these aspects of the operational definition of atypical AN. The high baseline average of these ED cognitions in our sample is consistent with other studies of patients with atypical AN (Johnson-Munguia et al, 2024). Inconsistent with previous research that has found associations between ED symptomatology and depressive disorders (Bodell et al, 2012;Brand-Gothelf et al, 2014) due to measurement-related variance in that predictors and outcomes come from the same self-report measure.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Endorsing these cognitive aspects of AN was also highly correlated with the severity of weight loss, but not the time frame of weight loss, highlighting the complexity and importance of further research to delineate these aspects of the operational definition of atypical AN. The high baseline average of these ED cognitions in our sample is consistent with other studies of patients with atypical AN (Johnson-Munguia et al, 2024). Inconsistent with previous research that has found associations between ED symptomatology and depressive disorders (Bodell et al, 2012;Brand-Gothelf et al, 2014) due to measurement-related variance in that predictors and outcomes come from the same self-report measure.…”
Section: Discussionsupporting
confidence: 91%
“…While this has decreased the prevalence of OSFED as desired (Lindvall Dahlgren et al, 2017;Machado et al, 2013), the natural taxonomic progression and increased awareness has resulted in increased prevalence of atypical AN and thus confusion around its operational definition (Masheb et al, 2021). The results of the current study are consistent with previous research in demonstrating the severity of ED cognitions and depressive symptomatology in atypical AN (e.g., Bachner-Melman et al, 2023;Johnson-Munguia et al, 2024), and the lack of association between a larger pretreatment weight loss (>10%) and Eating Concern, Restraint, or depressive symptoms (Forney et al, 2017). This study was novel in noting the lack of association between a shorter weight loss time frame (≤3 months) and Eating Concern, Restraint, or depressive symptoms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…AN and atypical AN are currently described as separate psychiatric disorders (American Psychiatric Association, 2022). However, recent meta-analyses found more similarities than differences between these two disorders (Johnson-Munguia et al, 2024;Walsh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…To a mind already sensitized to quantification and binaries, anorexia nervosa felt 'pure' and legitimized while atypical-alien, other (uncannily reflecting the diagnostic category it sits within). And our health systems convey this; the experiences of people with anorexia who are not 'clinically' underweight are often doubted, invalidated and nullified as they are 'not sick enough' (Barko & Moorman, 2023) when indeed, they are (Johnson-Munguia et al, 2024). This minimization and pathologization of people with higher weight anorexia can delay identification and treatment, trigger relapses and hinder people's recovery (Harrop et al, 2023) which is deeply concerning as while termed 'atypical', higher weight anorexia is as common if not more so than anorexia nervosa (Harrop et al, 2021).…”
mentioning
confidence: 99%